2022
DOI: 10.3389/fonc.2022.732860
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine Regulates Tumor-Associated Macrophages to Prevent Lung Cancer Angiogenesis Through the WNT/β-Catenin Pathway

Abstract: Tumor-associated macrophage (TAM)-mediated angiogenesis in the tumor microenvironment is a prerequisite for lung cancer growth and metastasis. Therefore, targeting TAMs, which block angiogenesis, is expected to be a breakthrough in controlling the growth and metastasis of lung cancer. In this study, we found that Sanguinarine (Sang) inhibits tumor growth and tumor angiogenesis of subcutaneously transplanted tumors in Lewis lung cancer mice. Furthermore, Sanguinarine inhibited the proliferation, migration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…[25][26][27] Monocytes were found to differentiate into tumor-associated macrophages, which could secrete tumor necrosis factor alpha and vascular endothelial growth factor to facilitate tumor angiogenesis, inflammatory response, and metastases. 28,29 Lymphocytes are crucial components of anticancer immunity and immune surveillance. 30 Downregulation of peripheral lymphocytes impairs the host's anticancer immunity and correlates with poor survival in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Monocytes were found to differentiate into tumor-associated macrophages, which could secrete tumor necrosis factor alpha and vascular endothelial growth factor to facilitate tumor angiogenesis, inflammatory response, and metastases. 28,29 Lymphocytes are crucial components of anticancer immunity and immune surveillance. 30 Downregulation of peripheral lymphocytes impairs the host's anticancer immunity and correlates with poor survival in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils could influence tumor development and progression via promoting tumor angiogenesis, aiding tumor cells to evade immune surveillance, and secreting large amounts of reactive oxygen species and nitric oxide 25–27 . Monocytes were found to differentiate into tumor‐associated macrophages, which could secrete tumor necrosis factor alpha and vascular endothelial growth factor to facilitate tumor angiogenesis, inflammatory response, and metastases 28,29 . Lymphocytes are crucial components of anticancer immunity and immune surveillance 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent in‐depth research has revealed the expanding pharmacological repertoire of SNG, encompassing its antimicrobial, anti‐inflammatory and antihypertensive effects (Ma, Sun, et al, 2017). In recent years, a substantial body of research has demonstrated that SNG is an effective anticancer drug, exhibiting significant antitumour effects through various targets and pathways in multiple cancer types, including gastric cancer (Pallichankandy et al, 2015), prostate cancer (Rahman et al, 2019), lung cancer (Cui et al, 2022), colorectal cancer (Malla & Bhamidipati, 2022), bladder cancer (Han et al, 2013), breast cancer (Su et al, 2021), pancreatic cancer (Ma, Yu, et al, 2017) and human leukaemia (Kuttikrishnan et al, 2019). However, the precise anticancer mechanism of SNG in osteosarcoma remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SNG has been found to induce autophagy by impeding lysosome formation and inhibiting autophagosome degradation, thereby impeding the progression of various cancers (Su et al, 2020; J. Wang, Su, et al, 2021). Moreover, SNG exhibits a pivotal role in inhibiting angiogenesis and regulating cellular migration and invasion, which are critical processes in cancer progression (Cui et al, 2022; Su et al, 2019). Despite its well‐established efficacy in numerous cancer types, there remains a scarcity of studies investigating the potential of SNG in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Sanguinarine reduces the MDSC accumulation, weakens the immunosuppressive ability of MDSCs, promotes the differentiation of MDSCs (differentiated into macrophages and DC), and increases the anti-lung-cancer immune response ( 133 ). In addition, sanguinarine has the potential to act as a novel regulator of the Wnt/β-catenin signaling pathway, modulating M2 macrophage polarization and inhibiting angiogenesis, both of which have potential application values in LC immunotherapy therapy ( 134 ).…”
Section: Anticancer Effects Of Natural Products When Targeting Tumor ...mentioning
confidence: 99%